Electrode for alkali metal ion battery as well as preparation method and application of electrode

By using polyimide polymer as a decentralized adhesive, the decentralization of conductive agent and the thermal stability of the electrode material are improved, and the dispersability of the in -battery electrode material is poor and the thermal stability of the adhesive is insufficient. The problem improves the electrochemical performance and cycle life of the battery.

CN119361697APending Publication Date: 2025-01-24SOUTH CHINA UNIV OF TECH +2

Patent Information

Application Number
CN202411446879.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Among the existing alkali metal ion battery electrode materials, poor dispersion of the conductive agent and insufficient thermal stability of the binder lead to poor electrochemical performance, which limits the improvement of battery performance.

Method used

Polyimide polymer is used as the dispersion binder, and the dispersion of the conductive agent is improved through the dispersion of its precursor polyamic acid, and the rigid-flexible combination structure of the polyimide polymer improves its thermal properties. stability and mechanical stability.

Benefits of technology

It significantly improves the conductive properties of the electrode and the cycle life of the battery, meeting the needs of electric vehicles for high energy density and low-cost batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361697A_ABST
    Figure CN119361697A_ABST
Patent Text Reader

Abstract

The invention discloses an electrode for an alkali metal ion battery as well as a preparation method and application of the electrode. The electrode comprises 8-12 parts by weight of a dispersion binder, the dispersion binder is a polyimide polymer, the polyimide polymer is obtained by imidization of a polyamide acid polymer, and the polyamide acid polymer is obtained by polymerization of aliphatic diamine, aromatic diamine and aromatic dianhydride; the electrode for the alkali metal ion battery also comprises the following components in parts by weight: 75-85 parts of an active substance; and 8-12 parts of a conductive agent. According to the electrode for the alkali metal ion battery, the polyimide polymer serves as a binding agent during electrode preparation and serves as a dispersing agent of the conductive agent, the phenomena of agglomeration, sedimentation and the like of the conductive agent can be avoided, additional materials do not need to be added, increase of inactive substances is avoided, and the service life of the electrode is prolonged. Therefore, the energy density of the battery is improved, and the performance of the battery is optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to an electrode for an alkali metal ion battery and a preparation method and application thereof. Background Art

[0002] Electric vehicles have put forward higher requirements for battery performance, especially in terms of energy density and battery cost. Lithium-ion batteries are composed of positive electrodes, negative electrodes, separators and electrolytes. The positive and negative electrode materials are the key components of battery materials. The preparation of electrode materials is generally carried out by preparing slurry and coating it on the current collector. Therefore, the quality of battery slurry directly affects the electrode coating quality, which in turn affects the electrochemical performance of the battery. In the slurry preparation process, there are the following problems: (1) The active material and the conductive agent have poor dispersion in the slurry and are easy to precipitate. In particular, the carbon nanotube conductive agent is difficult to disperse in the slurry. (2) Commercial binders such as polyvinylidene fluoride (PVDF) have poor thermal stability, are not resistant to high pressure and high temperature, are easy to oxidize, and have low adhesion. They are easy to polymerize with carbon black or active materials with small particle size, resulting in uneven dispersion and easy formation of gel. These problems have seriously affected the electrochemical performance of the battery, thereby restricting the improvement of battery performance. Summary of the invention

[0003] Therefore, it is necessary to provide an alkali metal ion battery electrode with good dispersibility of a conductive agent in the electrode and good conductivity, as well as a preparation method and application thereof.

[0004] The present invention adopts the following technical solutions:

[0005] An electrode for an alkali metal ion battery comprises the following components in parts by weight: 8-12 parts of a dispersing binder; 75-85 parts of an active material; and 8-12 parts of a conductive agent.

[0006] The dispersed binder is a polyimide polymer, which is obtained by imidization of a polyamic acid polymer, which is obtained by polymerization of an aliphatic diamine, an aromatic diamine and an aromatic dianhydride.

[0007] In the present invention, the polyimide polymer can play the role of a binder on the one hand, and its precursor polyamic acid can be used as a dispersant when preparing the electrode slurry on the other hand, and has a good dispersing effect on the conductive agent, which is beneficial to the dispersion of the conductive agent and the construction of a conductive network, thereby improving the conductivity of the electrode. In addition, the polyimide polymer in the present invention has excellent mechanical properties, chemical stability and thermal stability, and still has good thermal stability at a temperature of about 200°C. The polyimide polymer in the present invention introduces a flexible structural unit into the main chain of polyimide (PI), and the flexible structural unit mainly comes from the raw material aromatic diamine, thereby enhancing the flexibility and solubility of the polyimide molecular chain.

[0008] In addition, the polyimide polymer in the present invention introduces a rigid benzene ring structure in the main chain of polyimide (PI), and the rigid structural unit can come from the raw material aromatic diamine or aromatic dianhydride, which enhances the mechanical stability and thermal stability of the dispersion adhesive. At the same time, the carbonyl group in the PI segment enhances the affinity of the dispersion adhesive with alkali metal ions. The rigid-flexible polyimide polymer can not only be fully dissolved in NMP, but also resist the volume change of the electrode. In addition, the dispersing and solubilizing effect of the polyimide polymer on the conductive agent helps to achieve uniform dispersion of the electrode slurry. By adjusting the content of the flexible group in the polyimide polymer, polyimide polymers with different rigid-flexible ratios can be obtained, and then a dispersion adhesive with a variety of electrochemical properties and dispersion effects can be obtained.

[0009] Further, the aromatic dianhydride is one of the following: pyromellitic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, bicyclo(2.2.2)oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxybenzene)hexafluoropropane dianhydride, 4,4'-(4,4'-isopropylbenzeneoxy)bis(naphthalene dicarboxylic anhydride), biphenyltetracarboxylic dianhydride, diphenyl ether tetracarboxylic dianhydride;

[0010] The aliphatic diamine is one of the following: 1,2-bis(2-aminoethoxy)ethane, 1,3-propylenediamine, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, [poly(dimethylsiloxane), bis(3-aminopropyl) end-capping];

[0011] The aromatic diamine is one of the following: 2,4-diaminobenzoic acid, 3,4-diaminobenzoic acid, 3,5-diaminobenzoic acid, and 2,5-diaminoterephthalic acid.

[0012] Furthermore, the conductive agent is one of the following: acetylene black, conductive carbon black, carbon nanotubes, graphene, and Ketjen black.

[0013] Furthermore, the ratio of the total molar number of the aliphatic diamine and the aromatic diamine to the molar number of the aromatic dianhydride is 0.98-1.2:1;

[0014] The mass of the aliphatic diamine is 70-90% of the total mass of all diamines.

[0015] In the present invention, the total molar number of the aliphatic diamine and the aromatic diamine added is close to or greater than the molar number of the aromatic dianhydride added, thereby reducing the length of the polymer chain and preparing a low molecular weight polyamic acid (whose weight average molecular weight is less than 5000).

[0016] Furthermore, the active material is a positive electrode active material or a negative electrode active material.

[0017] Furthermore, the positive electrode active material includes one of the following: lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium nickel cobalt aluminum oxide;

[0018] When the electrode is applied to a positive electrode, a positive electrode active material may be added to the electrode.

[0019] The negative electrode active material includes one of the following: nano silicon, micro silicon, silicon oxygen, and silicon carbon.

[0020] When the electrode is applied to a negative electrode, a negative electrode active material may be added to the electrode.

[0021] The present invention also discloses a method for preparing the electrode for an alkali metal ion battery, which comprises the following steps:

[0022] S1: under an inert atmosphere, adding an aromatic dianhydride, an aliphatic diamine, and an aromatic diamine into a first organic solvent, and prepolymerizing at 10-50° C. with stirring for 4-24 hours to obtain a polyamic acid polymer; the ratio of the total molar sum of the aliphatic diamine and the aromatic diamine to the molar sum of the aromatic dianhydride is 0.98-1.2:1;

[0023] S2: After mixing 8-12 parts by weight of the polyamic acid polymer, 8-12 parts by weight of the conductive agent and the active material, a second organic solvent is added to adjust the viscosity to prepare an electrode slurry;

[0024] S3: forming a film of the electrode slurry on the current collector, then heating the mixture to 250-350° C., calcining the mixture for 1-5 hours, and performing an imidization reaction to obtain the electrode for the alkali metal ion battery.

[0025] In the present invention, the benzene ring structure in the polyamic acid polymer can form a π-π interaction with the conductive agent, thereby improving the agglomeration problem of the conductive agent in the electrode slurry. The polyamic acid polymer undergoes an imidization reaction in step S3 to form a polyimide polymer, which can act as a binder on the one hand and disperse the conductive agent on the other hand, acting as a dispersant, significantly improving the agglomeration of the conductive agent, especially the difficulty in dispersing carbon nanotubes. Therefore, the polyimide polymer in the present invention can improve the performance and cycle life of the battery, meeting the urgent demand of the electric vehicle industry for more advanced and efficient battery technology.

[0026] In the above method, the S1 step is specifically: adding aromatic dianhydride, aliphatic diamine, and aromatic diamine to a first organic solvent, prepolymerizing at 10-50°C with stirring for 4-24 hours to obtain a prepolymerization product, pouring the prepolymerization product into ethanol for precipitation, filtering, and drying the filter cake to obtain the polyamic acid polymer.

[0027] Furthermore, in the step S2, 80-110 parts by weight of active material is added, a second organic solvent is added to adjust the viscosity, and the components are mixed evenly to obtain an electrode slurry;

[0028] In the above method, the step S3 is specifically: uniformly coating the electrode slurry on the current collector to form a film with a thickness of 50-100 μm, drying to remove the second organic solvent to obtain the electrode sheet to be treated, and then calcining the electrode sheet at 250-350° C. for 1-5 hours to perform an imidization reaction to obtain the electrode for the alkali metal ion battery.

[0029] Further, the first organic solvent is one of the following: N-methylpyrrolidone, N-ethylpyrrolidone;

[0030] The second organic solvent is one of the following: N-methylpyrrolidone and N-ethylpyrrolidone.

[0031] Furthermore, in step S3, the heating rate is 3-8°C / min.

[0032] The present invention also provides an application of an electrode for an alkali metal ion battery. The electrode for an alkali metal ion battery is used for preparing an alkali metal ion battery.

[0033] The alkali metal ion battery includes a lithium ion battery, a sodium ion battery or a potassium ion battery.

[0034] The beneficial effects of the present invention are as follows: the alkali metal ion battery electrode of the present invention uses a polyimide polymer as a binder during electrode preparation on the one hand, and as a dispersant for a conductive agent on the other hand, which can avoid the phenomena of conductive agent agglomeration and sedimentation, and does not require additional materials, thereby avoiding the increase of inactive substances, thereby helping to improve the energy density of the battery and optimize battery performance. In addition, the polyimide polymer adopts a rigid-flexible structural design, so that it has good thermal stability and mechanical stability, and maintains good solubility and dispersion effect. The rigid structure improves the thermal stability of the polyimide polymer as a binder and optimizes the π-π interaction with the carbon nanotubes. The flexible chain segment improves the solubility of the polyimide polymer and ensures its good dispersion effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1This is a real picture of the carbon nanotube mixed solution prepared with polyamic acid in Example 1-3 after being left to stand for 30 days.

[0036] Figure 2 This is a real picture of the carbon nanotube mixed solution prepared with polyamic acid in Example 4-6 after being left to stand for 30 days.

[0037] Figure 3 It is the ultraviolet spectrum of the polyamic acid prepared in Example 1-3.

[0038] Figure 4 It is a standard curve of absorbance of carbon nanotubes with different concentrations in the embodiment of the present invention.

[0039] Figure 5 This is a test diagram of the dispersion performance of the polyamic acid prepared in Examples 1-6 on carbon nanotubes.

[0040] Figure 6 This is the infrared spectrum of the polyimide powder (PAA after imidization) in Example 1-3.

[0041] Figure 7 It is the differential scanning calorimetry test diagram of the polyimide powder (PAA after imidization) in Examples 1-3 and Comparative Example 1.

[0042] Figure 8 This is a peel strength test diagram of the positive electrode sheets in Examples 1-3 and Comparative Example 1.

[0043] Fig. 9 The figure shows the rate performance of the batteries in Examples 1-3 and Comparative Example 1 at different current densities and the long cycle performance at 2C. DETAILED DESCRIPTION

[0044] In order to explain the technical content, structural features, achieved objectives and effects of the technical solution in detail, the following is a detailed description in conjunction with specific embodiments and accompanying drawings.

[0045] Example 1

[0046] This example provides a method for preparing a lithium ion battery, which comprises the following steps (wherein, steps S1-S3 prepare an electrode for a lithium ion battery):

[0047] S1: Preparation of polyamic acid: 14mmol of 1,2-bis(2-aminoethoxy)ethane and 6mmol of diamine monomer of 3,5-diaminobenzoic acid were dissolved in 60mL of N-methylpyrrolidone (NMP), nitrogen was continuously introduced, and 20.4mmol of dianhydride monomer isomerate anhydride was added in batches under a 50°C water bath for 30 minutes to dissolve it, and nitrogen was introduced in a vacuum for 4 hours to obtain a polyamic acid polymer solution. After the reaction was completed, the polyamic acid polymer solution was poured into a large amount of ethanol to precipitate, and the obtained precipitate was centrifuged and vacuum dried for 12 hours to obtain a polyamic acid solid powder.

[0048] S2, preparation of positive electrode sheet: lithium iron phosphate (LFP), conductive carbon black, and binder (polyamic acid powder prepared in step S1) are mixed in a mass ratio of 8:1:1 to obtain slurry, NMP (0.2g) is added, and the slurry is evenly coated on aluminum foil with a thickness of 100μm. First, it is placed in a blast drying oven at 60℃ for 2 hours to remove most of the organic solvent, and then moved to a vacuum drying oven at 80℃ for 12 hours to obtain a positive electrode sheet to be processed.

[0049] S3, imidization of polyamic acid: punch the positive electrode sheet to be treated into small discs of 12 mm, then put the small discs into a quartz boat of a tubular furnace, introduce inert gas (nitrogen or argon), program the temperature to rise by 5°C / min, and calcine at 300°C for 2 hours to convert the polyamic acid into polyimide, thereby obtaining a positive electrode sheet containing a polyimide dispersed binder.

[0050] S4, battery assembly: The battery assembly is carried out in a glove box filled with argon gas, and is assembled into CR2032 button cells, which are lithium-ion batteries in this example.

[0051] Example 2

[0052] The only difference between the preparation method of the lithium ion battery in this example and that in Example 1 is that step S1 is different, specifically:

[0053] S1, preparation of polyamic acid: 16mmol of 1,2-bis(2-aminoethoxy)ethane and 4mmol of diamine monomer of 3,5-diaminobenzoic acid were dissolved in 60mL of N-methylpyrrolidone, nitrogen was continuously introduced, and 20.4mmol of dianhydride monomer pyromellitic anhydride was added in batches after stirring for 30 minutes in a 50°C water bath to dissolve it, and nitrogen was introduced in a vacuum for 4 hours to obtain a polyamic acid polymer solution. After the reaction was completed, the polymer solution was poured into a large amount of ethanol to precipitate, and the obtained precipitate was centrifuged and vacuum dried for 12 hours to obtain a polyamic acid solid powder.

[0054] Example 3

[0055] The only difference between the preparation method of the lithium ion battery in this example and that in Example 1 is that step S1 is different, specifically:

[0056] S1, preparation of polyamic acid: 18mmol of 1,2-bis(2-aminoethoxy)ethane and 2mmol of diamine monomer of 3,5-diaminobenzoic acid were dissolved in 60mL of N-methylpyrrolidone, nitrogen was continuously introduced, stirred in a water bath at 50°C for 30 minutes to dissolve it, and then 20.4mmol of dianhydride monomer pyromellitic anhydride was added in batches, and nitrogen was introduced in a vacuum for 4 hours to obtain a polyamic acid polymer solution. After the reaction was completed, the polymer solution was poured into a large amount of ethanol to precipitate, and the obtained precipitate was centrifuged and vacuum dried for 12 hours to obtain a polyamic acid solid powder.

[0057] Example 4

[0058] The only difference between the preparation method of the lithium ion battery in this example and that in Example 1 is that step S1 is different, specifically:

[0059] S1, preparation of polyamic acid: 15.4mmol of 1,2-bis(2-aminoethoxy)ethane and 6.6mmol of diamine monomer of 3,5-diaminobenzoic acid were dissolved in 60mL of N-methylpyrrolidone, nitrogen was continuously introduced, stirred in a water bath at 50°C for 30 minutes to dissolve it, and then 20mmol of dianhydride monomer pyromellitic anhydride was added in batches, and nitrogen was introduced in a vacuum for 4 hours to obtain a polyamic acid polymer solution. After the reaction was completed, the polymer solution was poured into a large amount of ethanol to precipitate, and the obtained precipitate was centrifuged and vacuum dried for 12 hours to obtain a polyamic acid solid powder.

[0060] Example 5

[0061] The only difference between the preparation method of the lithium ion battery in this example and that in Example 1 is that step S1 is different, specifically:

[0062] S1, preparation of polyamic acid: 17.6mmol of 1,2-bis(2-aminoethoxy)ethane and 4.4mmol of diamine monomer of 3,5-diaminobenzoic acid were dissolved in 60mL of N-methylpyrrolidone, nitrogen was continuously introduced, stirred in a water bath at 50°C for 30 minutes to dissolve it, and then 20mmol of dianhydride monomer pyromellitic anhydride was added in batches, and nitrogen was introduced in a vacuum for 4 hours to obtain a polyamic acid polymer solution. After the reaction was completed, the polymer solution was poured into a large amount of ethanol to precipitate, and the obtained precipitate was centrifuged and vacuum dried for 12 hours to obtain a polyamic acid solid powder.

[0063] Example 6

[0064] The only difference between the preparation method of the lithium ion battery in this example and that in Example 1 is that step S1 is different, specifically:

[0065] S1, preparation of polyamic acid: 21.6mmol of 1,2-bis(2-aminoethoxy)ethane and 2.4mmol of diamine monomer of 3,5-diaminobenzoic acid were dissolved in 60mL of N-methylpyrrolidone, nitrogen was continuously introduced, stirred in a water bath at 10°C for 30 minutes to dissolve it, and then 20mmol of dianhydride monomer pyromellitic anhydride was added in batches, and nitrogen was introduced in a vacuum for 24 hours to obtain a polyamic acid polymer solution. After the reaction was completed, the polymer solution was poured into a large amount of ethanol to precipitate, and the obtained precipitate was centrifuged and vacuum dried for 12 hours to obtain a polyamic acid solid powder.

[0066] The reaction equation for preparing the polyimide in Examples 1-6 is as follows:

[0067]

[0068] Example 7

[0069] This example provides a method for preparing a lithium ion battery, which comprises the following steps (wherein, steps S1-S3 prepare an electrode for a lithium ion battery):

[0070] S1: Preparation of polyamic acid: 14 mmol of 1,3-propylenediamine and 6 mmol of diamine monomer of 3,4-diaminobenzoic acid were dissolved in 60 mL of N-methylpyrrolidone (NMP), nitrogen was continuously introduced, and 20.4 mmol of 3,4,9,10-perylenetetracarboxylic dianhydride was added in batches after stirring in a water bath at 20°C for 30 minutes to dissolve it, and nitrogen was introduced in a vacuum for 20 hours to obtain a polyamic acid polymer solution. After the reaction was completed, the polyamic acid polymer solution was poured into a large amount of ethanol to precipitate, and the obtained precipitate was centrifuged and vacuum dried for 12 hours to obtain a polyamic acid solid powder.

[0071] S2, preparation of positive electrode sheet: lithium manganese oxide, acetylene black, and binder (polyamic acid powder prepared in step S1) are mixed in a mass ratio of 85:12:12 to obtain slurry, NMP (0.2g) is added, and the slurry is evenly coated on aluminum foil with a thickness of 50μm. First, it is placed in a blast drying oven at 60°C for 2 hours to remove most of the organic solvent, and then moved to a vacuum drying oven at 80°C for 12 hours to obtain a positive electrode sheet to be processed.

[0072] S3, imidization of polyamic acid: punch the positive electrode sheet to be treated into small discs of 12 mm, then put the small discs into a quartz boat in a tubular furnace, introduce inert gas (nitrogen or argon), program the temperature to rise by 5°C / min, and calcine at 350°C for 1 hour to convert the polyamic acid into polyimide, thereby obtaining a positive electrode sheet containing a polyimide dispersed binder.

[0073] S4, battery assembly: The battery assembly is carried out in a glove box filled with argon gas, and is assembled into CR2032 button cells, which are lithium-ion batteries in this example.

[0074] Example 8

[0075] This example provides a method for preparing a lithium ion battery, which comprises the following steps (wherein, steps S1-S3 prepare an electrode for a lithium ion battery):

[0076] S1: Preparation of polyamic acid: 14 mmol of 1,3-bis(3-aminopropyl)tetramethyldisiloxane and 6 mmol of diamine monomer of 2,4-diaminobenzoic acid were dissolved in 60 mL of N-methylpyrrolidone (NMP), nitrogen was continuously introduced, and 20.4 mmol of 1,2,3,4-cyclobutanetetracarboxylic dianhydride was added in batches after stirring for 30 minutes in a water bath at 40°C to dissolve it, and nitrogen was introduced in a vacuum to react for 10 hours to obtain a polyamic acid polymer solution. After the reaction was completed, the polyamic acid polymer solution was poured into a large amount of ethanol to precipitate, and the obtained precipitate was centrifuged and vacuum dried for 12 hours to obtain a polyamic acid solid powder.

[0077] S2, preparation of positive electrode sheet: lithium cobalt oxide, carbon nanotubes, and binder (polyamic acid powder prepared in step S1) are mixed in a mass ratio of 75:10:10 to obtain slurry, NMP (0.2g) is added, and the slurry is evenly coated on aluminum foil with a thickness of 70μm. First, it is placed in a blast drying oven at 60°C for 2 hours to remove most of the organic solvent, and then moved to a vacuum drying oven at 80°C for 12 hours to obtain a positive electrode sheet to be processed.

[0078] S3, imidization of polyamic acid: punch the positive electrode sheet to be treated into small discs of 12 mm, then put the small discs into a quartz boat of a tubular furnace, introduce inert gas (nitrogen or argon), program the temperature to rise by 5°C / min, and calcine at 250°C for 5 hours to convert the polyamic acid into polyimide, thereby obtaining a positive electrode sheet containing a polyimide dispersed binder.

[0079] S4, battery assembly: The battery assembly is carried out in a glove box filled with argon gas, and is assembled into CR2032 button cells, which are lithium-ion batteries in this example.

[0080] Example 9

[0081] This example provides a method for preparing a lithium ion battery, which comprises the following steps (wherein, steps S1-S3 prepare an electrode for a lithium ion battery):

[0082] S1: Preparation of polyamic acid: 14 mmol of [poly(dimethylsiloxane), bis(3-aminopropyl) end-capping] and 6 mmol of diamine monomer of 2,5-diaminoterephthalic acid were dissolved in 60 mL of N-methylpyrrolidone (NMP), nitrogen was continuously introduced, and 20.4 mmol of biphenyltetracarboxylic dianhydride was added in batches after stirring for 30 minutes in a 30°C water bath to dissolve it. Nitrogen was introduced in a vacuum and reacted for 15 hours to obtain a polyamic acid polymer solution. After the reaction was completed, the polyamic acid polymer solution was poured into a large amount of ethanol to precipitate, and the obtained precipitate was centrifuged and vacuum dried for 12 hours to obtain a polyamic acid solid powder.

[0083] S2, preparation of positive electrode sheet: nano silicon, graphene, and binder (polyamic acid powder prepared in step S1) are mixed in a mass ratio of 80:8:8 to obtain slurry, NMP (0.2g) is added, and the slurry is evenly coated on aluminum foil with a thickness of 90μm. First, it is placed in a blast drying oven at 60°C for 2 hours to remove most of the organic solvent, and then moved to a vacuum drying oven at 80°C for 12 hours to obtain a negative electrode sheet to be processed.

[0084] S3, imidization of polyamic acid: punch the negative electrode sheet to be treated into small discs of 12 mm, then put the small discs into a quartz boat of a tubular furnace, introduce inert gas (nitrogen or argon), program the temperature to rise by 3°C / min, and calcine at 300°C for 2 hours to convert the polyamic acid into polyimide, thereby obtaining a negative electrode sheet containing a polyimide dispersed binder.

[0085] S4, battery assembly: The battery assembly is carried out in a glove box filled with argon gas, and is assembled into CR2032 button cells, which are lithium-ion batteries in this example.

[0086] Comparative Example 1

[0087] This example provides a lithium ion battery, which is prepared by the following preparation method, specifically:

[0088] S1, preparation of positive electrode sheet: lithium iron phosphate (LFP), conductive carbon black, and binder (PVDF) were mixed in a mass ratio of 8:1:1, NMP (0.2g) was added, and the slurry was evenly coated on aluminum foil with a thickness of 100μm. First, it was placed in a blast drying oven at 60℃ for 2 hours to remove most of the organic solvent, and then moved to a vacuum drying oven at 80℃ for 12 hours to obtain an LFP-PVDF positive electrode sheet.

[0089] S2, battery assembly: The battery is assembled in a glove box filled with argon gas into CR2032 button cells, which are lithium-ion batteries in this example.

[0090] Performance Testing:

[0091] (1) Static test

[0092] First, carbon nanotubes (CNTs) were added to NMP to prepare a carbon nanotube solution with a CNTs concentration of 0.8 mg / mL; the polyamic acid (PAA) prepared in step S1 of Examples 1-3 was added to NMP to prepare a pure PAA solution with a PAA concentration of 0.8 mg / mL; then the polyamic acid prepared in Examples 1-3 was added to the above carbon nanotube solution to prepare polyamic acid mixed solutions of different concentrations, so that the amount of polyamic acid added was 0%, 10%, 50%, and 100% of the mass of CNTs, and the above prepared solutions were left to stand at room temperature for 30 days, and then observed whether stratification or precipitation occurred in the solution, as shown in detail. Figure 1 As shown, Figure 1 Middle (a), Figure 1 (b) and Figure 1 (c) are the actual pictures of the polyamic acid mixed solutions of different concentrations in Example 1, Example 2 and Example 3 after standing for 30 days. Figure 1 Middle (a), Figure 1 (b) and Figure 1 In (c), the mass percentages of PAA from left to right are 0%, 10%, 50%, 100%, and pure PAA solution.

[0093] Depend on Figure 1 It can be seen that the mass ratio of flexible diamine to rigid diamine in polyamic acid of Example 1 is 7:3. The carbon nanotubes dispersed with different contents of polyamic acid did not show any sedimentation phenomenon after standing for 30 days, showing good dispersibility. The content of rigid diamine in polyamic acid of Examples 2-3 was reduced, and carbon nanotubes were dispersed with polyamic acid of 50% and 100% by mass, and different degrees of stratification occurred, and the NMP solution containing only CNTs also showed obvious sedimentation. This is mainly because the rigid diamine content in the embodiment is high. Since the rigid diamine contains more conjugated structures, it can effectively interact with the surface of CNTs by π-π, so that it remains suspended without sedimentation. Therefore, by controlling the mass ratio of flexible diamine to rigid diamine in polyamic acid, the dispersibility of the conductive agent can be controlled to a certain extent.

[0094] In addition, no stratification was observed in the dispersed carbon nanotube solutions when the mass fraction of polyamic acid in Examples 1-3 was 10% after standing for 30 days, while the mixed solutions obtained by dispersing carbon nanotubes with polyamic acid in Examples 2-3 with mass percentages of 50% and 100% showed stratification after standing for 30 days, which shows that the amount of polyamic acid added also affects the dispersion of carbon nanotubes. Too much polyamic acid may cause aggregation and accumulation, making the distance between carbon nanotubes smaller, thereby increasing the possibility of agglomeration. In addition, pure PAA can be completely dissolved in NMP, which proves the good solubility of the prepared polyamic acid in NMP.

[0095] First, carbon nanotubes (CNTs) were added to NMP to prepare a carbon nanotube solution with a CNTs concentration of 0.8 mg / mL; the polyamic acid (PAA) prepared in step S1 of Example 4-6 was added to NMP to prepare a pure PAA solution with a PAA concentration of 0.8 mg / mL; then the polyamic acid prepared in Example 4-6 was added to the carbon nanotube solution to prepare polyamic acid mixed solutions of different concentrations, and the amount of polyamic acid added was 10%, 50%, and 100% of the mass of CNTs. The prepared solution was left to stand at room temperature for 30 days, and then observed whether stratification or precipitation occurred in the solution, as shown in FIG. Figure 2 As shown, Figure 2 Middle (a), Figure 2 (b) and Figure 2 (c) are the actual pictures of the polyamic acid mixed solutions of different concentrations in Example 4, Example 5 and Example 6 after standing for 30 days. Figure 2 Middle (a), Figure 2 (b) and Figure 2 In (c), the mass percentages of PAA from left to right are 10%, 50%, 100%, and pure PAA solution. Figure 2 It can be seen that after the mixed solutions of polyamic acid with different concentrations prepared by using the polyamic acid in Examples 4-6 were left standing for 30 days, no obvious sedimentation phenomenon occurred, which showed a good dispersion effect on carbon nanotubes.

[0096] (2) Dispersion performance test

[0097] The Lambert-Beer law method was used to determine the dispersion of polyamic acid on carbon nanotubes. The specific test method is as follows:

[0098] S1, UV spectrum test of polymer. In order to eliminate the influence of characteristic absorption peak of polymer on carbon nanotube test, the range outside the absorption band of polymer is selected as the UV measurement range of carbon nanotube concentration. Specifically, the polyamic acid prepared in Examples 1-3 is first prepared into a solution (using NMP as solvent), and then UV spectrum test is performed. The specific test results are shown in FIG. Figure 3 As shown by Figure 3 It can be seen that the characteristic absorption peak of polyamic acid is between 200-400nm. Outside this wavelength range, the measurement range outside the carbon nanotube concentration is selected, that is, the measurement wavelength is selected as 500nm.

[0099] S2, measuring the UV absorption spectra of carbon nanotubes of different concentrations. 4 mg, 8 mg, 12 mg, 18 mg, and 20 mg of carbon nanotubes were respectively placed in 1 L of NMP, and then ultrasonically treated for 2 hours, and then directly tested by UV. According to the Lambert-Beer law, the absorbance measured at 500 nm and the carbon nanotube concentration were paired, and a standard curve was drawn, as shown in the following figure. Figure 4 shown.

[0100] S3, the polyamic acid prepared in Examples 1-3 was selected and mixed with carbon nanotubes and NMP at a concentration of 10 mg:10 mg:10 mL. After ultrasonic treatment for 2 hours, the ultraviolet absorbance of each solution at 500 nm was immediately measured, and the CNT concentration was analyzed by absorbance to evaluate the dispersion effect. The specific test results are as follows: Figure 5 As shown, at the same time, a control group was set up. The control group was mixed with carbon nanotubes and NMP at a concentration of 10 mg:10 mL. The ultraviolet absorbance of the solution at 500 nm was immediately measured after 2 hours of ultrasound. The CNT concentration was analyzed by absorbance to evaluate the dispersion effect of the control group. Figure 5 shown.

[0101] Depend on Figure 5 It can be seen that the dispersion concentrations of the polyamic acid prepared in Examples 1-6 for carbon nanotubes are 22 mg / L, 8 mg / L, 5 mg / L, 10 mg / L, 6 mg / L, and 5 mg / L, respectively, and the dispersion concentration of the control group for carbon nanotubes is 5 mg / L. Among them, the dispersion degree of PAA prepared in Examples 1 and 4 for carbon nanotubes is higher than that of other examples. This is because the rigid benzene ring structure content in these polymers is higher, which improves the π-π interaction between the polymer and the carbon nanotubes, so the dispersion ability is stronger. In addition, -COOH and -NH- in PAA form hydrogen bonds with the oxygen-containing functional groups in CNTs, and the combined action of these chemical bonds improves the dispersion effect of CNTs in the solution.

[0102] (3) Infrared spectrum test

[0103] The polyamic acid powder prepared in step S1 of Example 1-3 is further imidized to obtain polyimide powder. The infrared spectra of the polyimide powders prepared in Examples 1-3 are tested respectively. The specific test results are as follows: Figure 6 As shown, Figure 6 There are characteristic functional groups of polyimide in the -1 and 1770cm -1The symmetric and asymmetric stretching vibration peaks at 1393 cm represent the C=O bond in the imide ring. -1 The peak at 726 cm corresponds to the stretching vibration of the CN bond. -1 The peak at 3500cm corresponds to the out-of-plane bending vibration of the imine ring. -1 The left and right correspond to the stretching vibration of OH in the carboxyl group. The appearance of these characteristic groups indicates the successful preparation of the polyimide in Examples 1-3.

[0104] (4) Thermal stability test

[0105] The DSC curves of the polyimide powders in Examples 1-3 and Comparative Example 1 were tested respectively. The specific test results are as follows: Figure 7 As shown. Figure 7 It can be seen that the PVDF adhesive used in Comparative Example 1 exhibits an obvious endothermic peak at 164°C, while the polyimide adhesive used in Examples 1-3 does not exhibit an obvious endothermic peak in the range of 25-200°C, indicating that the synthesized polyimide adhesive is always in an amorphous state.

[0106] (5) Peel strength test

[0107] The peel strength of the positive electrode sheets in Examples 1-3 and Comparative Example 1 was tested respectively. The specific test results are as follows: Figure 8 As shown. Figure 8 It can be seen that the peel strengths of Examples 1-3 and Comparative Example 1 are 0.93 KN / m, 0.74 KN / m, 1.55 KN / m, and 1.61 KN / m, respectively. It is particularly noteworthy that the highly flexible diamine polyimide (such as Example 3) binder electrode has a relatively high peel strength. This phenomenon can be attributed to the fact that the flexible segments rich in polyimide can provide more hydrogen bonding groups, thereby forming stronger bonding sites with the active material components and promoting bonding.

[0108] (6) Battery cycle performance test

[0109] The rate performance and long cycle performance of the lithium ion batteries at different current densities in Examples 1-3 and Comparative Example 1 were tested respectively. The rate performance test conditions were as follows: first, the battery was cycled 10 times at a current density of 0.2C (1C = 170 mA hg -1 ), and then cycled five times at 0.5C, 1C, 2C, 3C, 4C, and 0.2C respectively, with a voltage range of 2.5-3.7V. The specific test results are as follows Fig. 9 As shown, Fig. 9 (a) is the rate performance test diagram under different current densities; Fig. 9 (b) is a long cycle performance test diagram at 2C. Fig. 9The vertical axis “Specific Capacity” represents the specific capacity, the “Coulombiceffiency” represents the coulombic efficiency, and the horizontal axis “Cycle number” represents the cycle number.

[0110] Depend on Fig. 9 It can be seen that at a low rate of 0.2C, the specific capacities of the batteries in Examples 1-3 and Comparative Example 1 are similar. However, as the current density increases from 0.2C to 4C, the specific capacities of the batteries in Examples 1, 2, and 3 reach 79 mA h g -1 、82mA hg -1 and 88mA hg -1 , which is significantly higher than the 74mA hg of the battery in Comparative Example 1 -1 When the current density decreases, the specific capacity of the batteries of Examples 1-3 can also recover rapidly, showing good rate performance and reversibility. In addition, in the 200-cycle performance test at 2C current density, Examples 1-3 all showed good cycle stability, with capacities of 92 mAh g -1 , 105mAh g -1 , 102mAh g -1 , compared with 94 mAh g of the battery using PVDF binder in Comparative Example 1. -1 The capacity values ​​are comparable, and some embodiments even perform better, which further verifies the application potential of polyimide as a binder.

[0111] In summary, the alkali metal ion battery in the present invention adopts polyimide polymer as a dispersing adhesive, which has the characteristics of high temperature and high pressure resistance and good bonding performance. At the same time, the precursor polyamic acid of the adhesive acts as a dispersing adhesive for the conductive agent during the pulping process, thereby achieving stable dispersion of the conductive agent, promoting the formation of a conductive network in the electrode material, and further improving the rate performance of the battery.

[0112] It should be noted that, although the above embodiments have been described in this article, the patent protection scope of the present invention is not limited thereby. Therefore, based on the innovative concept of the present invention, changes and modifications made to the embodiments described herein, or equivalent structures or equivalent process changes made using the contents of the present invention specification and drawings, directly or indirectly applying the above technical solutions to other related technical fields, are all included in the patent protection scope of the present invention.

Claims

1. An electrode for an alkali metal ion battery, characterized in that: The composition comprises the following components in parts by weight: Dispersed binder 8-12 parts; Active substance 75-85 parts; Conductive agent 8-12 parts; The dispersed binder is a polyimide polymer, which is obtained by imidization of a polyamic acid polymer, which is obtained by polymerization of an aliphatic diamine, an aromatic diamine and an aromatic dianhydride.

2. An electrode for an alkali metal ion battery according to claim 1, characterized in that: The aromatic dianhydride is one of pyromellitic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, bicyclo(2.2.2)oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxybenzene)hexafluoropropane dianhydride, 4,4'-(4,4'-isopropylenediphenoxy)bis(naphthalene dicarboxylic anhydride), biphenyltetracarboxylic dianhydride or diphenyl ether tetracarboxylic dianhydride; The aliphatic diamine is one of 1,2-bis(2-aminoethoxy)ethane, 1,3-propylenediamine, 1,3-bis(3-aminopropyl)tetramethyldisiloxane or [poly(dimethylsiloxane), bis(3-aminopropyl) end-capped]; The aromatic diamine is one of 2,4-diaminobenzoic acid, 3,4-diaminobenzoic acid, 3,5-diaminobenzoic acid or 2,5-diaminoterephthalic acid.

3. The electrode for an alkali metal ion battery according to claim 1, characterized in that: The conductive agent is one of acetylene black, conductive carbon black, carbon nanotubes, graphene or Ketjen black.

4. The electrode for an alkali metal ion battery according to claim 2, characterized in that: The ratio of the total molar number of the aliphatic diamine and the aromatic diamine to the molar number of the aromatic dianhydride is 0.98-1.2:1; The mass of the aliphatic diamine is 70-90% of the total mass of all diamines.

5. The electrode for an alkali metal ion battery according to claim 1, characterized in that: The active material is a positive electrode active material or a negative electrode active material.

6. The electrode for an alkali metal ion battery according to claim 5, characterized in that: The positive electrode active material includes one of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide or lithium nickel cobalt aluminum oxide; The negative electrode active material includes one of nano silicon, micro silicon, silicon oxide or silicon carbon.

7. The method for preparing an electrode for an alkali metal ion battery according to any one of claims 1 to 6, characterized in that: It includes the following steps: S1: adding aromatic dianhydride, aliphatic diamine and aromatic diamine to a first organic solvent under an inert atmosphere, and prepolymerizing at 10-50° C. for 4-24 hours under stirring to obtain a polyamic acid polymer; S2: After mixing the polyamic acid polymer, the conductive agent and the active material, a second organic solvent is added to adjust the viscosity to prepare an electrode slurry; S3: forming a film of the electrode slurry on the current collector, then heating the mixture to 250-350° C., calcining the mixture for 1-5 hours, and performing an imidization reaction to obtain the electrode for the alkali metal ion battery.

8. The preparation method according to claim 7, characterized in that: The step S1 specifically comprises: adding aromatic dianhydride, aliphatic diamine and aromatic diamine into a first organic solvent, prepolymerizing at 10-50° C. with stirring for 4-24 hours to obtain a prepolymerized product, pouring the prepolymerized product into ethanol for precipitation, filtering and drying the filter cake to obtain the polyamic acid polymer.

9. The preparation method according to claim 7, characterized in that: The step S3 specifically comprises: uniformly coating the electrode slurry on the current collector to form a film with a thickness of 50-100 μm, drying to remove the second organic solvent to obtain the electrode sheet to be treated, and then calcining the electrode sheet at 250-350° C. for 1-5 hours to perform an imidization reaction to obtain the electrode for the alkali metal ion battery.

10. The electrode according to any one of claims 1 to 6 is used in the preparation of an alkali metal ion battery.

Citation Information

Patent Citations

  • Polyimide binder for positive electrode of lithium ion battery, preparation method and application thereof

    CN109755582A

  • Blending type polyamide acid solution, blending type polyimide adhesive, battery pole piece and preparation method of battery pole piece

    CN114752074A

  • Polyimide-coated lithium ion battery positive electrode material, preparation method and application

    CN116914101A

  • Self-repairing polyimide and application thereof in lithium ion battery

    CN118271630A

Cited By

  • Positive pole piece, preparation method thereof and lithium ion battery

    CN121149162A